2022
DOI: 10.1186/s12936-022-04157-y
|View full text |Cite
|
Sign up to set email alerts
|

Blood meal profile and positivity rate with malaria parasites among different malaria vectors in Sudan

Abstract: Background Malaria is a life-threatening public health problem globally with particularly heavy burden in the sub-Saharan Africa including Sudan. The understanding of feeding preference of malaria vectors on different hosts is a major challenge for hindering the transmission cycle of malaria. In this study, blood meals taken by blood-fed Anopheles mosquitoes collected from the field in malaria endemic areas of Sudan were analysed for source of blood meal and malaria parasite presence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In Nouakchott, until proven otherwise, malaria parasites are transmitted exclusively by An. arabiensis, which can transmit both P. vivax and P. falciparum, as demonstrated in other African countries where P. vivax and P. falciparum are sympatric [43][44][45]. It is therefore not easy to understand why P. falciparum has been responsible for only a minority of malaria infections in Nouakchott until present.…”
Section: Discussionmentioning
confidence: 99%
“…In Nouakchott, until proven otherwise, malaria parasites are transmitted exclusively by An. arabiensis, which can transmit both P. vivax and P. falciparum, as demonstrated in other African countries where P. vivax and P. falciparum are sympatric [43][44][45]. It is therefore not easy to understand why P. falciparum has been responsible for only a minority of malaria infections in Nouakchott until present.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed a slightly higher proportion of females who tested positive for malaria in comparison to males. While similar ndings have been reported earlier [31], this may be due to more complex behaviours, such as sleeping indoors, which may offer to some extent protection against outdoor vector biting [4,27]. Generally, one who spent time outside are more susceptible to malaria infection than their counterparts [32].…”
Section: Discussionmentioning
confidence: 53%
“…This con rms the heterogeneity of malaria transmission in Sudan. This heterogeneity is mainly in uenced by the proportional distribution of the risk factors such as climate, geography, and socio-economic status, as well as environmental conditions, abundance of the various vectors, as well as socioeconomic characteristics, local risky behaviours and practices [10,27,33]. Several studies have also reported similar variations in malaria prevalence across the different regions in Sudan [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a substantial number of the origins of Anopheles blood meals were not identified using human and bovine antibodies. This may indicate that different blood meal sources exist for malaria mosquitoes as documented in Sudan [ 36 ]. As a result, considering all wild animals, including cattle, could have provided a better understanding of the sources of Anopheles blood meals in the study area.…”
Section: Discussionmentioning
confidence: 99%